Некоторые наблюдения о новой эмиграции: образ, практики, тексты - Posokhin, Ivan (Studia Rossica Posnaniensia, 2025)
This article examines the emergence of a new Russian émigré community following the full-scale Russian invasion of Ukraine in 2022. It explores several ways of how this wave of emigration constructs its collective identity through cultural practices and discourse, mostly drawing on parallels with historical emigration waves. The research highlights the discursive construction of émigré self-perception, emphasizing its moral and cultural opposition to the political climate in Russia. This opposition also functions as a strategy for self-legitimization and adaptation in host societies. The study investigates the role of literature, media, and institutional structures within the new émigré community, particularly the emergence of a new “tamizdat”. Key arguments include the instrumentalization of historical analogies, the evolution of émigré discourse, and the interplay between ethical, aesthetic, and political dimensions. The article concludes that this new emigration is not merely a demographic and political phenomenon but also a discursive one, shaping narratives of cultural exile.